2012
DOI: 10.4314/wsa.v38i2.13
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pH on the adsorption of lead by Na-clinoptilolite: Kinetic and equilibrium studies

Abstract: The objectives of this study were, firstly, to establish the mechanism by which modified clinoptilolite (in Na form) adsorbs lead ions and, secondly, to assess the extent of influence of pH on the adsorption capacity. To this end, the experimental data have been fitted by adsorption isotherms, thermodynamic and kinetic models. Based on the standard errors obtained during experiments, it was determined that the accuracy of prediction of the isotherm models considered for adsorption decreases in the order: Dubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 38 publications
(26 reference statements)
3
13
0
Order By: Relevance
“…The E value for Cu(II) on the sesame husk is 0.316 kJ/mol. The value of E is below 8 kJ/mol which indicates that physical adsorption is involved in the adsorption process [88] As seen in Table 3 This is in line with results reported by Cozmuta et al [174] who studied the adsorption of lead metal ions on Na-clinoptilolite and by Li et al [175] who studied the adsorption of Cu(II) ions on amino-functionalized magnetic nanoparticles. Table 4.…”
Section: Dubinin-radushkevich (D-r) Isothermsupporting
confidence: 79%
“…The E value for Cu(II) on the sesame husk is 0.316 kJ/mol. The value of E is below 8 kJ/mol which indicates that physical adsorption is involved in the adsorption process [88] As seen in Table 3 This is in line with results reported by Cozmuta et al [174] who studied the adsorption of lead metal ions on Na-clinoptilolite and by Li et al [175] who studied the adsorption of Cu(II) ions on amino-functionalized magnetic nanoparticles. Table 4.…”
Section: Dubinin-radushkevich (D-r) Isothermsupporting
confidence: 79%
“…Metal removal involved the mechanisms of both adsorption and ion exchange. This occurred via bulk diffusion of metal ions from the solution to the zeolite surfaces, intra-particle diffusion of metal ions through the zeolite macro pores and meso pores to the microcrystal surfaces where they replaced some of the exchangeable framework cations, adsorption on the internal surfaces of the zeolites and possibly precipitation on the surface of the zeolite due to increase in pH [2,22,[42][43][44]. There was an observed increase in the pH of effluent solutions from 5.5 to 6.30.…”
Section: Metal Removal Performancementioning
confidence: 99%
“…Under certain conditions, there is an increase in removal efficiency with increased pH (Chaouch et al 2014;Zeng et al 2015); at high pH, the adsorbent surface assumes a net negative charge, which favours the attraction and subsequent adsorption of positively charged ions. Cozmuta et al (2012) observed that lead complexes favoured at low pH have smaller hydrated radii and are therefore more mobile than the normal lead ion. Moreover, as pH increases, competition for adsorption sites ensues between the hydrogen ion and the lead ion, thus reducing adsorption efficiency.…”
Section: Efficiency Of Lead Adsorption By Rhamentioning
confidence: 97%